Sleep quality and reproductive health in physically active women - the literature review - Milewska-Plis, Katarzyna; Kłak, Igor; Szerocki, Jan; Nowakowska, Wiktoria; Bartnik, Katarzyna; Chwaleba, Katarzyna; Mazur, Ksenia; Karalus, Monika; Curyło, Weronika; Grudina, Alina (Quality in Sport, 2025)
Sleep plays a crucial role in maintaining women's reproductive health, as it regulates the secretion of key hormones within the hypothalamic-pituitary-gonadal (HPG) axis and modulates inflammatory processes. This literature review explores the complex, bidirectional relationships between sleep, the menstrual cycle, and fertility in physically active women. Physiological mechanisms, including the roles of melatonin, cortisol, and sex steroids, are discussed in the context of sleep architecture. Moreover, the review highlights how moderate physical activity generally promotes better sleep quality, while excessive or poorly planned exercise can disrupt sleep patterns, elevate cortisol levels, and impair reproductive function. The prevalence of sleep disorders—such as insomnia, restless legs syndrome, and circadian rhythm misalignment—among female athletes is examined, with emphasis on their underdiagnosis and potential consequences for performance and health. Non-pharmacological strategies, including behavioral interventions, sleep hygiene education, and sleep tracking technologies, are proposed as first-line measures to improve sleep quality and reduce the risk of menstrual irregularities and infertility. Pharmacological treatments are also mentioned as a complementary approach in complex cases. Finally, the review identifies gaps in current research and underscores the importance of integrating sleep management into the care of physically active women to safeguard both reproductive and overall health.